Technology-assisted cardiac rehabilitation for coronary heart disease patients with central obesity: a randomized controlled trial - Su, Jing-Jing; Wong, Arkers-Kwan-Ching; Zhang, Li-Ping; Bayuo, Jonathan; Lin, Rose; Abu-Odah, Hammoda; Batalik, Ladislav (European journal of physical and rehabilitation medicine, 2024)
BACKGROUND: Limited empirical evidence is available regarding the effect of technology-assisted cardiac rehabilitation (TACR) among coronary heart disease (CHD) patients with central obesity. AIM: To determine the effects of 12-week TACR on health outcomes of patients with CHD. DESIGN: Two-arm randomized controlled trial. SETTING: Cardiovascular department of a regional hospital. POPULATION: Coronary heart disease patients with central obesity. METHODS: The study randomized 78 hospitalized CHD patients to receive either the 12-week TACR intervention or usual care. Guided by social cognitive theory, the intervention began with an in-person assessment and orientation session to assess and identify individual risks and familiarize with the e-platform/device before discharge. After discharge, patients were encouraged to visit the interactive CR website for knowledge and skills acquisition, data uploading, use the pedometer for daily step tracking, and interact with peers and professionals via social media for problem-solving and mutual support. Data were collected at baseline (T0), six-week (T1), and 12-week (T2). RESULTS: Participants in the intervention group showed significant improvement in daily steps at six weeks but not 12 weeks (T1: β=2713.48, P=0.03; T2:β=2450.70, P=0.08), weekly sitting minutes (T1: β=-665.17, P=0.002; T2: β=-722.29, P=0.02), and total (vigorous, moderate, and walking) exercise at 12-week (β=-2445.99, P=0.008). Improvement in health-promoting lifestyle profile (T1: β=24.9, P<0.001; T2: β=15.50, P<0.001), smoking cessation (T2: β=-2.28, P<0.04), self-efficacy (T2: β=0.63, P=0.02), body mass index (T1:β =-0.97, P=0.03; T2: β=-0.73, P=0.04) and waist circumferences (T1: β =-1.97, P=0.003; T2: β =-3.14, P=0.002) were identified. CONCLUSIONS: Results indicated the effectiveness of the TACR intervention in improving healthy behaviors and anthropometric parameters for CHD patients with central obesity. Individual assessment, collaborative action planning, and ongoing obesity management support should be highlighted in TACR programs for CHD patients. CLINICAL REHABILITATION IMPACT: Central obesity should be assessed and highlighted in TACR intervention as an independent risk factor that requires corresponding behavior change and body fat management.
Keywords: zdravé chování; Coronary Disease; Humans; cvičení; Obesity, Abdominal; kardiovaskulární rehabilitace; lidé; abdominální obezita; Cardiac Rehabilitation; Exercise; Health Behavior; koronární nemoc